Prevalence and Associated Factors of Burnout Risk among Emergency Nurses during COVID-19 Pandemic - I Made Dwie Pradnya Susila; Ida Ayu Agung Laksmi (Babali Health, 2022)
Introduction: The Emergency Department (ED) nurses are the first health care professionals to treat patients infected during COVID-19 pandemic. The workload of ED nurses is quite heavy because generally patients who are rushed to the ED are emergency patients who need to get health services as quickly and accurately as possible. This study aimed to determine the prevalence and associated factors of burnout risk among Emergency Nurses during COVID-19 pandemic in Bali. Methods: A cross-sectional study was carried out on the risk of burnout among emergency nurses in Bali. This research was conducted in June 2021 involving 85 emergency nurses who are members of the Indonesian emergency and disaster nurse association in Bali. The instrument used to identify the nurses’ burnout is the Maslach Burnout Inventory Indonesian version. Statistical analysis was carried out using the Spearman Rank test with a level of significance (α<0.05). Results: The ED nurses burnouts during the COVID-19 pandemic in Bali have average burnout ranged from 9.8 to 34.58. Most of the respondents (72.9%) were in mild emotional exhaustion, 69.4% experienced moderate depersonalization and 45.9% had low personal accomplishment. Hospital resource have co-morbidities and previous experience of treating patients with infectious diseases statistically correlated with ED nurses burnouts.